2020
DOI: 10.3390/su12229768
|View full text |Cite
|
Sign up to set email alerts
|

Do Corporate Environmental Sustainability Practices Influence Firm Value? The Role of Independent Directors: Evidence from Saudi Arabia

Abstract: Environmental sustainability has become a significant approach for firms to enhance their competitive advantage and reputation. This study examines the association between environmental sustainability disclosures and firm value, in addition to the moderating impact of independent board directors on this association. Using data from Saudi listed firms, we find that reporting environmental sustainability practices has a positive and significant impact on firm value, suggesting that enhanced responsibility and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 87 publications
3
19
0
3
Order By: Relevance
“…In a similar fashion, Kilincarslan, Elmagrhi, and Li [47] conducted a study to ascertain the influence of corporate governance on environmental sustainability reporting and concluded that proxies of corporate governance are positive and have significant influence on companies' environmental sustainability reporting practices. The findings are in like manner to past studies results [2,13,26,30,40,50,52,67].…”
Section: Review Of Extant Literaturesupporting
confidence: 91%
“…In a similar fashion, Kilincarslan, Elmagrhi, and Li [47] conducted a study to ascertain the influence of corporate governance on environmental sustainability reporting and concluded that proxies of corporate governance are positive and have significant influence on companies' environmental sustainability reporting practices. The findings are in like manner to past studies results [2,13,26,30,40,50,52,67].…”
Section: Review Of Extant Literaturesupporting
confidence: 91%
“…When focal firms implement proactive environmental protection strategies and create green environmental values, cooperation with suppliers and consumers is necessary (Ammer et al. , 2020).…”
Section: Theoretical Background and Hypothesis Researchmentioning
confidence: 99%
“…When focal firms implement proactive environmental protection strategies and create green environmental values, cooperation with suppliers and consumers is necessary (Ammer et al, 2020). The green environmental value of sustainable development is generated during the consumption of products or services, so suppliers must provide green supplies to generate green value (Vargo and Lusch, 2008).…”
Section: Green Innovation and Value Cocreationmentioning
confidence: 99%
“…In achieving sustainable performance, all parts of an organization have to be involved, starting from the low-level management to the highlevel management, including stakeholders. Sustainable performance mostly depends on corporate governance quality because effective corporate governance will maintain the trust of stakeholders (Ammer et al, 2020). This will be useful in obtaining prospective investors and realizing the future goals of an organization.…”
Section: Introductionmentioning
confidence: 99%